2022
DOI: 10.21831/jk.v10i2.52392
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physical exercise on vital lung capacity in Tapak Suci athletes

Abstract: Exercise can have a physiological effect on the body, including the work system of the heart and lungs. The lungs have an important role in human life, where there is an exchange of oxygen with carbon dioxide through the respiratory process. In terms of health, exercise needs to be done by every human being, because exercise can increase the work of the lung muscles, whereas if the lung muscles work well, the ability to accommodate oxygen or the vital capacity of the human lungs also increases. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In this study, we examined how age and physical activity affected the spirometry reference values. Numerous researches have confirmed that there is a linear link in the case of children and adolescents when age is preserved as the independent variable [6][7][8][9][10] . A favorable correlation between age and spirometry metrics including FVC, FEV1, PEFR, and FEF25-75% has also been shown in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined how age and physical activity affected the spirometry reference values. Numerous researches have confirmed that there is a linear link in the case of children and adolescents when age is preserved as the independent variable [6][7][8][9][10] . A favorable correlation between age and spirometry metrics including FVC, FEV1, PEFR, and FEF25-75% has also been shown in recent studies.…”
Section: Discussionmentioning
confidence: 99%